Embryonic Thermal Manipulation Affects Ventilation, Metabolism, Thermal Control and Central Dopamine in Newly Hatched and Juvenile Chicks - Rocha, Aline C. G.; Cristina-Silva, Caroline; Taxini, Camila L.; da Costa Silva, Kaoma Stephani; Lima, Virgínia T. M.; Macari, Marcos; Bícego, Kênia C.; Szawka, Raphael E.; Gargaglioni, Luciane H. (Frontiers in Physiology, 2021)
The first third of incubation is critical for embryonic development, and environmental changes during this phase can affect the physiology and survival of the embryos. We evaluated the effects of low (LT), control (CT), and high (HT) temperatures during the first 5 days of incubation on ventilation (VE), body temperature (Tb), oxygen consumption (VO2), respiratory equivalent (VE/VO2), and brain monoamines on 3-day-old (3d) and 14-day-old (14d) male and female chickens. The body mass of LT animals of both ages and sexes was higher compared to HT and CT animals (except for 3d males). The heart mass of 14d HT animals was higher than that of CT animals. Thermal manipulation did not affect VE, VO2 or VE/VO2 of 3d animals in normoxia, except for 3d LT males V ̇E, which was lower than CT. Regarding 14d animals, the HT females showed a decrease in V ̇E and V ̇O2 compared to CT and LT groups, while the HT males displayed a lower V ̇O2 compared to CT males, but no changes in V ̇E/V ̇O2. Both sexes of 14d HT chickens presented a greater Tb compared to CT animals. Thermal manipulations increased the dopamine turnover in the brainstem of 3d females. No differences were observed in ventilatory and metabolic parameters in the 3d animals of either sexes, and 14d males under 7% CO2. The hypercapnic hyperventilation was attenuated in the 14d HT females due to changes in V ̇O2, without alterations in V ̇E. The 14d LT males showed a lower V ̇E, during hypercapnia, compared to CT, without changes in V ̇O2, resulting in an attenuation in VE/VO2. During hypoxia, 3d LT females showed an attenuated hyperventilation, modulated by a higher VO2. In 14d LT and HT females, the increase in V ̇E was greater and the hypometabolic response was attenuated, compared to CT females, which resulted in no change in the VE/VO2. In conclusion, thermal manipulations affect hypercapnia-induced hyperventilation more so than hypoxic challenge, and at both ages, females are more affected by thermal manipulation than males.